2018
DOI: 10.3390/su10072516
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the Promotion of Prefabricated Construction in China

Abstract: Prefabricated construction has been proven effective, environmentally-friendly, and labor-friendly. It is widely considered a sustainable approach to the construction industry. China is still in the initial process of adopting prefabricated construction practices and has conducted a few studies to date on the constraints of prefabricated construction up to the operation stage. This paper focuses on the major factors obstructing prefabricated construction development in China. Twenty-three variables affecting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 38 publications
2
54
0
1
Order By: Relevance
“…Since prefabricated buildings have contributed greatly to the global fight against the new coronavirus "COVID-19", they have again attracted global attention. Prefabricating buildings has long been considered a sustainable practice in the architecture, engineering, and construction (AEC) industries [1], and involves moving a partially finished building from a construction site into a controlled component factory [2]. Other terms related to prefabricated buildings include prefabrication [3], industrialized buildings [4], precast buildings [5], prefabrication techniques [6], prefabricated…”
Section: Introductionmentioning
confidence: 99%
“…Since prefabricated buildings have contributed greatly to the global fight against the new coronavirus "COVID-19", they have again attracted global attention. Prefabricating buildings has long been considered a sustainable practice in the architecture, engineering, and construction (AEC) industries [1], and involves moving a partially finished building from a construction site into a controlled component factory [2]. Other terms related to prefabricated buildings include prefabrication [3], industrialized buildings [4], precast buildings [5], prefabrication techniques [6], prefabricated…”
Section: Introductionmentioning
confidence: 99%
“…Determine and review the work activities for unit production in factory (determine factory work) 1, 17, 27, 28, 29 23 Prepare shop drawings and check interference in unit production 22 24 Prepare unit production line design 23 25 Prepare manufacturing tolerance management plan 17, 22, 23, 26 26 Prepare quality management plan 22, 25…”
Section: Manufacturing 22mentioning
confidence: 99%
“…For example, if the Road Traffic Act regulations of an area are not considered in a related design step, the size of units may need to be reworked for transportation, which can cause schedule and cost overruns.In modular construction, the complexity involved makes identification of the information flows difficult [14]. To facilitate the integration of participants and identification of the information flows in the design phase of a modular project, an integrated design process is required to ensure that the project is managed considering the entire project process, including design, unit production, transportation, erection, and performance [22,23]. However, designs are still established based on conventional stick-built construction methods, which are unsuitable for modular construction, and lack of expertise and knowledge in the marketplace make it difficult to recognize the need for the integrated design process [18,22,24].…”
mentioning
confidence: 99%
“…Boafo et al pointed out that prefabrication improved the speed of construction, quality of architecture, efficiency of materials, and worker safety and limited the environmental impacts of construction [25]. Jiang et al found that IB efficiency has a positive effect on the economic factors, livability, safety, environmental factors, and social benefits [26]. Environmental performance evaluations are also of great interest to many researchers.…”
Section: Introductionmentioning
confidence: 99%